2011
DOI: 10.1158/0008-5472.can-10-3894
|View full text |Cite
|
Sign up to set email alerts
|

Novel Theranostic Opportunities Offered by Characterization of Altered Membrane Lipid Metabolism in Breast Cancer Progression

Abstract: Activation of lipid metabolism is an early event in carcinogenesis and a central hallmark of many cancers. However, the precise molecular composition of lipids in tumors remains generally poorly characterized. The aim of the present study was to analyze the global lipid profiles of breast cancer, integrate the results to protein expression, and validate the findings by functional experiments. Comprehensive lipidomics was conducted in 267 human breast tissues using ultraperformance liquid chromatography/ mass s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
396
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(430 citation statements)
references
References 30 publications
32
396
2
Order By: Relevance
“…SFA are less susceptible to lipid peroxidation, so they prevent the oxidative damage. Studies have correlated the increase of a saturated phosphatidylcholine with progression of breast cancer (Hilvo et al 2011). Lipids in cancer cells have key functions as signaling molecules or introducing posttranslational modifications in proteins.…”
Section: Resultsmentioning
confidence: 99%
“…SFA are less susceptible to lipid peroxidation, so they prevent the oxidative damage. Studies have correlated the increase of a saturated phosphatidylcholine with progression of breast cancer (Hilvo et al 2011). Lipids in cancer cells have key functions as signaling molecules or introducing posttranslational modifications in proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Small molecules and gene silencing (e.g. acetyl-CoA carboxylase alpha) were shown to be effective in inhibiting cancer cell proliferation and viability in vitro [77][78][79]. However, most experiments performed in monolayer cancer cell cultures do not accurately reflect the conditions found in in vivo, where the intercellular contact, tumor dynamics and overall heterogeneous microenvironment Fig.…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, inhibition of ACS amplifies antitumor effects. 31 The data in this study indicated that BAFF-R signaling on hepatocytes may have a role in the development and progression of liver cancer; nonetheless, further studies are necessary to substantiate this conclusion.…”
Section: Discussionmentioning
confidence: 99%